Relationship Between Teacher Professionalism and Performance in Elementary Schools - Dara Sartika; Muhammad Ihsan Dacholfany; Sujino Sujino (International Journal of Multidisciplinary Research of Higher Education, 2026)
This study investigates the relationship between certified teacher professionalism and teacher performance in elementary schools. A quantitative approach with a correlational design was employed. The sample consisted of 52 certified teachers selected through total sampling. Data were collected using a Likert-scale questionnaire that had been tested for validity and reliability. Pearson Product Moment correlation analysis was conducted with the aid of Microsoft Excel. The findings reveal a positive and significant relationship between certified teacher professionalism and teacher performance (r = 0.755 > r table = 0.273; p < 0.05), categorized as a strong correlation. Teacher professionalism contributed 57% to teacher performance. These results highlight the crucial role of enhancing teacher professionalism in improving performance within elementary education.